Diagnosis dan Tatalaksana Mata Kering - Faiq Razaan Razaan; Putu Ristyaning Ayu Sangging; Rani Himayani (CV. Jasa Sukses Abadi, 2023)
Dry eye disease is a multifactorial disease of the tears and the surface of the eye that gives rise to unsafe indications, visual problems, and tear film instability with the potential to damage the eye surface. This condition can be followed by an increase in tear film osmolarity and inflammation of the ocular surface. This dry eye can occur due to reduced aqueous humor fluid produced by the ciliary body or increased production of tear evaporation that occurs due to disruption of the function of the meibomian glands. Based on these triggers, dry eyes can be classified into two categories: dry eyes due to aqueous deficiency (MKDA) and evaporative dry eyes (MKE). The diagnosis of dry eye order of examination of dry eyes include a patient history using a questionnaire, tear film break-up time with fluorescein, eye surface staining using fluorescein or lissamine green, Schirmer I test with or without anesthesia, Schirmer II test with nasal stimulation, and eyelid examination. and meibomian glands. Treatment of dry eye disease can be pharmacological or non-pharmacological. The management of dry eye disease depends on the severity of the disease, An example of a drug for the management of dry eye disease is cendo lyters. Non-pharmacological treatment for preventing dry eye disease is avoiding its causes, such as vehicle fumes, limiting using gadget, and also being able to use sunglasses if there are indications of red and dry eyes. This paper uses the article review method by using sources such as journals. The purpose of this writing is to know the definition, diagnosis, and management of dry eye. The results of this paper found that the diagnosis of dry eyes can be established by history and physical examination. The conclusion obtained is that the management of dry eyes depends on the symptoms found in the history and physical examination.